Optimal antimalarial dose regimens for chloroquine in pregnancy based on population pharmacokinetic modelling - Salman, S.; Baiwog, F.; Page-Sharp, Madhu; Kose, K.; Karunajeewa, H.; Mueller, I.; Rogerson, S.; Siba, P.; Ilett, K.; Davis, T. (Elsevier Science, 2017)
Despite extensive use and accumulated evidence of safety, there have been few pharmacokinetic studies from which appropriate chloroquine (CQ) dosing regimens could be developed specifically for pregnant women. Such optimised CQ-based regimens, used as treatment for acute malaria or as intermittent preventive treatment in pregnancy (IPTp), may have a valuable role if parasite CQ sensitivity returns following reduced drug pressure. In this study, population pharmacokinetic/pharmacodynamic modelling was used to simultaneously analyse plasma concentration-time data for CQ and its active metabolite desethylchloroquine (DCQ) in 44 non-pregnant and 45 pregnant Papua New Guinean women treated with CQ and sulfadoxine/pyrimethamine or azithromycin (AZM). Pregnancy was associated with 16% and 49% increases in CQ and DCQ clearance, respectively, as well as a 24% reduction in CQ relative bioavailability. Clearance of DCQ was 22% lower in those who received AZM in both groups. Simulations based on the final multicompartmental model demonstrated that a 33% CQ dose increase may be suitable for acute treatment for malaria in pregnancy as it resulted in equivalent exposure to that in non-pregnant women receiving recommended doses, whilst a double dose would likely be required for an effective duration of post-treatment prophylaxis when used as IPTp especially in areas of CQ resistance. The impact of co-administered AZM was clinically insignificant in simulations. The results of past/ongoing trials employing recommended adult doses of CQ-based regimens in pregnant women should be interpreted in light of these findings, and consideration should be given to using increased doses in future trials.